2011
DOI: 10.1071/rd10270
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations in total antioxidant capacity, catalase activity and hydrogen peroxide levels of follicular fluid during bovine folliculogenesis

Abstract: Follicular fluid is an important environment for oocyte development, yet current knowledge regarding its in vivo oxidant and antioxidant levels remains limited. Examining follicular fluid oxidants and antioxidants will improve understanding of their changes in vivo and contribute to optimization of in vitro maturation conditions. The aim of our study was to consider select markers, namely catalase (CAT) enzyme activity, total antioxidant capacity (TAC), and hydrogen peroxide (H2O2) in follicular fluid samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 34 publications
1
36
0
2
Order By: Relevance
“…Oxidative stress occurs when the generation of ROS exceeds the scavenging capacity of antioxidants, either due to excessive ROS production or an inadequate availability of antioxidants. At physiological levels, ROS is required for reproductive functions including oocyte maturation, folliculogenesis, ovarian steroidogenesis, luteolysis, ovulation and cyclical endometrial changes [2] . However ROS, higher than physiological levels, contribute to several pathological conditions, such as retained placenta, udder oedema, mastitis, infertility which in turn may impair reproductive performances [3] .…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress occurs when the generation of ROS exceeds the scavenging capacity of antioxidants, either due to excessive ROS production or an inadequate availability of antioxidants. At physiological levels, ROS is required for reproductive functions including oocyte maturation, folliculogenesis, ovarian steroidogenesis, luteolysis, ovulation and cyclical endometrial changes [2] . However ROS, higher than physiological levels, contribute to several pathological conditions, such as retained placenta, udder oedema, mastitis, infertility which in turn may impair reproductive performances [3] .…”
Section: Introductionmentioning
confidence: 99%
“…Adicionalmente, é ainda possível que tenha ocorrido a exposição dos oócitos a fatores deletérios provenientes de folículos atrésicos, ou mesmo de maior diâmetro, já que durante a punção não era possível aferir de forma precisa o tamanho folicular. Outra característica relevante é a relação inversa entre a faixa etária e a concentração das enzimas envolvidas na desintoxicação de EROs, como a glutationa transferase, observada em humanos (28) e bovinos (29) . Como geralmente não se conhece a idade das vacas utilizadas nos distintos experimentos, é possível que este seja um importante fator responsável pelos resultados controversos em diferentes estudos sobre a composição e o efeito da utilização do LF durante a MIV.…”
Section: Resultsunclassified
“…Hennet and C.M.H. Combelles in bovine follicular fluid decrease with increasing follicle size (Combelles et al, 2010), although total antioxidant capacity (TAC) was reported to be highest in the follicular fluid of larger follicles (Gupta et al, 2011). These trends suggest that the antioxidant/ ROS balance in follicular fluid is actively and specifically adapted as folliculogenesis and oogenesis progress.…”
Section: Reactive Oxygen Species (Ros) and Antioxidantsmentioning
confidence: 93%